Odpowiedzi

2009-10-26T21:23:40+01:00
A)a-[a-(1-a)]=a-[a-1+a]=a-a+1-a=-a+1
b)-x-[-(1-x)-(x-1)]=-x-[-1+x-x+1]=-x+1-x+x-1=-x
c)x-[y-(x-y)-x-(y-x)]=x-[y-x+y-x-y+x]=x-y+x-y+x+y-x=2x-y
d)1-a-[1-(a-1)-2a-(1-3a)]-a-1=1-a-[1-a+1-2a-1+3a]-a-1=1-a-1+a-1+2a+1-3a-a-1=
=-2a-1
2009-10-26T21:32:09+01:00
A) a-[a-(1-a)]=
=a-(a-1+a)=
=a-(2a-1)=
=a-2a+1=
=-a+1
b) -x-[-(1-x)-(x-1)]=
=-x-(-1+x)-x+1=
=-x+1-x-x+1=
=-3x+2
c) x-[y-(x-y)-x-(y-x)]=
=x-(y-x+y-x-y+x)=
=x-(y-x)=
=x-y+x=
=2x-y
d) 1-a-[1-(a-1)-2a-(1-3a)]-a-1 =
=1-a-(1-a+1-2a-1+3a)-a-1=
=1-a-(1)-a-1=
=1-a-1-a-1=
=-2a-1